Screening of exopolysaccharide-producing Enterobacter aerogenes NJ1023 and its cadaverine biosynthesis promotion - Xie, Yanai; Ye, Zhen; Wan, Xin; Deng, Hua; Sun, Weihao; He, Xun; Chen, Kequan (Frontiers in Microbiology, 2023)
Enterobacter aerogenes, the gram-negative bacteria belonging to the family Enterobacteriaceae, lacks the ability to synthesize chemicals. However, in this study, a strain of Enterobacter aerogenes NJ1023 screened from the soil containing petrochemicals was found to be capable of producing extracellular polysaccharides (EPSs). After purification of the polysaccharide, the chemical composition and physicochemical properties of the polysaccharide were analyzed by UV–Vis spectra, FTIR spectroscopy and GC-MS, etc. The results showed that: The molecular weight of the polysaccharide produced by this strain was only 2.7×103 Da, which was lower than that reported in other polysaccharides from the same genus. The polysaccharide produced by E. aerogenes NJ1023 mainly comprised xylose, glucose, galactose, and N-acetylglucosamine with a molar ratio of 0.27: 4.52: 1.74: 0.2, which differed from those reported from the same genus. The results demonstrated that lower incubation temperatures and shaking speeds were more favorable for EPSs synthesis, while higher incubation temperatures and shaking speeds favored cell growth. Additionally, the EPSs produced by E. aerogenes NJ1023 significantly protected the Escherichia coli cells against cadaverine stress. Overall, the discovery of EPSs produced by E. aerogenes increased the diversity of bacterial polysaccharides and broadened the potential applications of this species.